A New Approach for Delivering eLearning Courses in Jordanian Universities - Atoum, Adnan; Al-Zoubi, Abdallah; Jaber, Majed Abu; Al-Dmour, Mamoun; Hammad, Bashar (Advances in Social Sciences Research Journal, 2017)
A new approach for delivering eLearning course in Jordanian universities is presented. The main objective of this experiment is to improve the quality and relevance of eLearning at Jordanian higher education institutions through the development, implementation and teaching of an English Language course at a national level. The pilot course was designed and delivered in four Jordanian universities under strict Quality Assurance (QA) measures over several consecutive semesters. The outcomes of the pilot ensured proper assimilation of eLearning QA standards and learning outcomes.